2022
DOI: 10.1039/d1tc05520h
|View full text |Cite
|
Sign up to set email alerts
|

Transforming polyethylene and polypropylene into nontraditional fluorescent polymers by thermal oxidation

Abstract: Polyolefins like polyethylene (PE) and polypropylene (PP) without any conventional or nonconventional fluorescent chromophores have never been considered as raw materials for the preparation of fluorescent polymers. Here we report...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…As depicted in Figure d,e, the novel peak that appeared at 3384 cm –1 corresponded to the −NH stretching vibration of the resulting amines of oxidized PEI, and −NH deformation vibration shifted from 1600 cm –1 of PEI to 1630 cm –1 in ohPEI. Furthermore, the bending vibration of −CH 2 of PEI banded at 1294 cm –1 changed to 1302 cm –1 , which was rationally attributed to the −CH 2 of ohPEI. ,, These indicated the successful oxidation of hPEI. Meanwhile, the peaks centered at 1437 and 1349 cm –1 were the characteristics of asymmetric stretching relaxion of B–O–C (Figure f), confirming the formation of borate ester.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…As depicted in Figure d,e, the novel peak that appeared at 3384 cm –1 corresponded to the −NH stretching vibration of the resulting amines of oxidized PEI, and −NH deformation vibration shifted from 1600 cm –1 of PEI to 1630 cm –1 in ohPEI. Furthermore, the bending vibration of −CH 2 of PEI banded at 1294 cm –1 changed to 1302 cm –1 , which was rationally attributed to the −CH 2 of ohPEI. ,, These indicated the successful oxidation of hPEI. Meanwhile, the peaks centered at 1437 and 1349 cm –1 were the characteristics of asymmetric stretching relaxion of B–O–C (Figure f), confirming the formation of borate ester.…”
Section: Resultsmentioning
confidence: 82%
“…Furthermore, the bending vibration of −CH 2 of PEI banded at 1294 cm −1 changed to 1302 cm −1 , which was rationally attributed to the −CH 2 of ohPEI. 30,34,37 These indicated the successful oxidation of hPEI. Meanwhile, the peaks centered at 1437 and 1349 cm −1 were the characteristics of asymmetric stretching relaxion of B−O−C (Figure 1f), 38 confirming the formation of borate ester.…”
Section: Fabrication and Characterization Of The Polymermentioning
confidence: 86%
See 1 more Smart Citation
“…Especially, the emission wavelength of the third-generation dendrimer is over 600 nm under the excitation wavelengths of 560 nm, which is caused by the formed larger heteroatom clusters. Increasing the oxygen density can also endow polymers with long-wavelength emissions. , Thus, a higher oxygen density will generate larger clusters and long-wavelength emissions. Yan et al found that the electron cloud of carbonyl and CC bonds in polysiloxane will overlap and form multiple through-space conjugation rings, and blue, green, and red light will be generated under different excitations; hence, the emission mechanism named multiring-induced multicolor emission is proposed .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found that some nonconventional luminogens without aromatic building blocks also exhibit a luminescent property. Meanwhile, the reported nonconventional luminescent materials show unique clustering-triggered emission (CTE) characteristics. Their emission behavior shows concentration-enhanced emission, aggregation-induced emission (AIE), and excitation wavelength dependence.…”
Section: Introductionmentioning
confidence: 99%